Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude

GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Juventude(s) e AIDS em Moçambique: Um Estudo Qualitativo no Distrito de Nhamatanda - Chicamisse, Francisco Armindo Zinhame (Universidade Federal de São Paulo, 2013)
O presente estudo pretende compreender como são desenvolvidas as ações de prevenção do HIV do Programa Geração Biz (PGB) direcionadas aos jovens dos 15-24 anos e, dessa forma buscar a compreensão da possível vulnerabilidade destes a infecção pelo HIV no distrito de Nhamatanda em Moçambique. Para o alcance deste desiderato baseei-me numa abordagem qualitativa, embasada no método etnográfico. No processo de coleta de dados privilegiei a observação participante, complementada por entrevistas semi-estruturadas e uma extensiva pesquisa bibliográfica. No distrito de Nhamatanda os jovens dos 15-24 anos constituem um dos segmentos populacionais mais afetados pelo HIV/AIDS, com uma taxa de prevalência estimada em 30,5% no ano de 2007, sendo por isso considerado um dos grupos mais vulneráveis a infecção pelo HIV. As ações de prevenção do HIV voltadas para este grupo são desenvolvidas pelo PGB, através das suas três componentes: escolar, comunitária e clínica. Entretanto, estas ações ainda estão assentadas na premissa de que a simples transmissão de informação implica na mudança de comportamentos dos jovens. Ademais, as ações de prevenção acabam tendo por vezes um caráter setorial e descontínuo, o que não permite o alcance de resultados mais duradouros no âmbito da prevenção do HIV. Os resultados deste estudo sugerem que as ações de prevenção do HIV ainda não se têm traduzido na redução considerável da referida vulnerabilidade dos jovens (15-24) a infecção pelo HIV neste distrito. Estas ações colocam por vezes os jovens em situações de maior suscetibilidade a infecção pelo HIV. Portanto, há uma necessidade de se repensar no modo como estas ações têm sido operacionalizadas, reelaborar os modelos pedagógicos que as norteiam e adequar os conteúdos semânticos das mensagens em função dos diferentes contextos socioculturais em que a epidemia se espraia.
Keywords: G - Mozambique / Moçambique; G - central / centro; GD - Nhamatanda; GP - Sofala; Health PEA; L - portuguese / português; access to services / acesso a serviços; health / saúde; youth / juventude